Influencing Factors of Hospital-Acquired Pneumonia Infection in the Middle-Aged and Elderly Patients With Schizophrenia - Yang, Mi; Li, Qiwen; Wang, Chunzhi; Li, Li; Xu, Min; Yan, Fei; Chen, Wei; Wan, Ying (Frontiers in Psychiatry, 2021)
Introduction Pneumonia is an important cause of death in patients with schizophrenia. It is critical to understand the risk factors of hospital-acquired pneumonia (HAP) and determine prevention strategies to reduce HAP. The aim of this study is to elucidate the risk factors for HAP in elderly hospitalized patients with schizophrenia. Methods We retrospectively reviewed the medical records of 2617 elderly patients (age ≥ 50) with schizophrenia who were admitted for the first time to a large scale psychiatric hospital between 2016 and 2020. The factors related to the incidence of HAP in patients were analyzed, including personal characteristics, antipsychotics, and non-antipsychotics. Results The HAP infection rate of hospitalized elderly patients with schizophrenia was 7.8%. Chi-square analyses showed that older age, male, and ≥ 60 days of hospitalization were risk factors for HAP infection (2 = 94.272, p < 0.001; 2 = 22.110, p < 0.001; 2 = 8.402, p = 0.004). Multivariate logistic regression showed that quetiapine, clozapine, and olanzapine significantly increased the incidence of HAP (OR = 1.56, 95% CI = 1.05-2.32, p = 0.029; OR =1.81, 95% CI = 1.26-2.60, p = 0.001; OR = 1.68, 95% CI = 1.16-2.42, p = 0.006). Antipsychotic drugs combined with aceglutamide had an effect on HAP (OR =2.19, 95%CI =1.38-3.47, p =0.001). Conclusion The high HAP infection rate in hospitalized elderly patients with schizophrenia may be related to the increase of age and the use of antipsychotic drugs. The types and dosages of antipsychotic drugs should be minimized while paying attention to the mental symptoms of patients.